Integralidade: um desafio para o processo regulatório em saúde no SUS - Oliveira, Aline Ferreira Sanches Solei de; Moraes, Amanda Cristina de; Junior, Fernando Oliveira Souza; Bruscalin, Gabrielle Giacomini; Pelliser Filho, Jose Eduardo; Miguel, Marisol Dias; Piaia, Letícia Cristina; Montalti, Nathalia Stein; Silva, Neila Kátia da; Galdino, Roberto; Lima, Viviana Aparecida de (Revista Acadêmica GUETO, 2024)
Projeto